Proximal Anterior Cruciate Ligament Tears: The Healing Response Technique versus Conservative Treatment - Wasmaier, Johann; Kubik-Huch, Rahel; Pfirrmann, Christian; Grehn, Holger; Bieg, Christian; Eid, Karim (The Journal of Knee Surgery, 2013)
The healing response technique (HRT) is a nonreconstructive method to promote healing in proximal anterior cruciate ligament (ACL) tears. The study reviews clinical and radiological long-term results. Thirty patients (average age 31 years) were treated according to the protocol described by Steadman et al. For comparison, an age- and gender-matched control group of conservatively treated patients (CST; n = 127) was selected. At follow-up (mean: 4 years), all patients were evaluated using Kneelax-3-arthrometer, magnetic resonance imaging (MRI), and by clinical examination. Two HRT patients were lost to follow-up and 10 (36%) patients needed definitive ACL reconstruction. The rate of secondary ACL reconstruction in the initial CST group was 56% (71 of 127). Nineteen of the conservatively treated patients were selected according to above-mentioned criteria. The average Lysholm score in the HRT group was 91 (CST group = 90), and the Orthopaedische Arbeitsgemeinschaft Knie score was 93 (CST group = 92). Tegner score decreased from 6.8 before injury to 5.7 at the time of follow-up (CST group: 6.0 to 5.1). Kneelax-3-arthrometer showed a significant higher anterior knee laxity compared with the noninjured side in both groups. MRI showed improvement of the ACL in both groups. HRT in adult patients is associated with a high revision rate of 36% secondary ACL reconstruction, comparable with primary conservative treatment (p = 0.056). For the remaining patients (64%), HRT did not result in better outcomes than conservative treatment.
Keywords: anterior cruciate ligament; knee; healing response; conservative treatment; magnetic resonance imaging